Hubungan Antara Faktor Klinis dengan Perilaku Self Management pada Pasien Hemodialisis di RSD K.R.M.T Wongsonegoro Semarang - Arnesya Tilameo; Merry Tiyas Anggraini; Hema Dewi Anggraheny (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Chronic Kidney Disease (CKD) is a condition characterized by an irreversible decline in kidney function, necessitating hemodialysis. Self-management is a crucial strategy in modifying the lifestyle of CKD patients undergoing hemodialysis. Several clinical factors, including disease duration, duration of hemodialysis, frequency of hemodialysis, complications, and comorbidities, influence self-management. This study aims to examine the relationship between clinical factors and self-management behavior in hemodialysis patients at RSD K.R.M.T Wongsononegoro, Semarang. This study used an analytical observational method with a cross-sectional approach. The sampling technique used was total sampling, involving 50 respondents. Data collection was conducted using a structured questionnaire and the Hemodialysis Patient Self-Care Measurement Scale. The relationship analysis was performed using the Spearman’s rank and mann-whitney test. The average duration of illness and hemodialysis among respondents was 32.92 months, with a mean self-management score of 64.02. All 50 respondents (100%) underwent hemodialysis twice a week. The majority of respondents experienced complications (n=45, 90%) and comorbidities (n=41, 82%). Spearman’s rank analysis indicated no significant relationship between disease duration and self-management (p=0.529) or between hemodialysis duration and self-management (p=0.529). The relationship between hemodialysis frequency and self-management could not be analyzed, as all patients underwent hemodialysis twice a week. Furthermore, the Mann-Whitney test showed no significant difference in self-management scores concerning complications (p=0.650) or comorbidities (p=0.960). There is no association between disease duration, duration of hemodialysis, frequency of hemodialysis, complications, and comorbidities with self-management behavior.